EFEKTIFITAS ANALISIS TUGAS UNTUK MENINGKATKAN KETERAMPILAN MEMBUAT PUDING RAINBOW PADA ANAK TUNARUNGU - Silvi Dinasty Arifin, Mega Iswari, Asep Ahmad Sopandi (Jurnal Penelitian Pendidikan Khusus, 2013)
this research is backround by problem that found a deaf child in second grade class in junior high school YPPLB that have a problem to make rainbow puding with the right step. According that problem, the researcher want to proof that analytic is efectifitas to improve the skill to make the puding rainbow for a deaf child in second grade at junior high school. This study uses the approach single research subject, A-B-A design and data analysis techniques using visual analysis chart. The result of this study concluded with analisis exercise can improve the skill to make a puding rainbow for a deaf child in a second grade in junior high school YPPLB Padang.